10-Year cardiovascular event risks for women who experienced hypertensive disorders in late pregnancy: the HyRAS study - Ponjee Gabrielle; Porath Martina; van der Post Joris A; Bloemenkamp Kitty W; van Pampus Maria G; Franx Arie; Hermes Wietske; Tamsma Jouke T; Mol Ben W; de Groot Christianne J (BMC, 2010)
Abstract Background Cardiovascular disease is the cause of death in 32% of women in the Netherlands. Prediction of an individual's risk for cardiovascular disease is difficult, in particular in younger women due to low sensitive and specific tests for these women. 10% to 15% of all pregnancies are complicated by hypertensive disorders, the vast majority of which develop only after 36 weeks of gestation. Preeclampsia and cardiovascular disease in later life show both features of "the metabolic syndrome" and atherosclerosis. Hypertensive disorders in pregnancy and cardiovascular disease may develop by common pathophysiologic pathways initiated by similar vascular risk factors. Vascular damage occurring during preeclampsia or gestational hypertension may contribute to the development of future cardiovascular disease, or is already present before pregnancy. At present clinicians do not systematically aim at the possible cardiovascular consequences in later life after a hypertensive pregnancy disorder at term. However, screening for risk factors after preeclampsia or gestational hypertension at term may give insight into an individual's cardiovascular risk profile. Methods/Design Women with a history of preeclampsia or gestational hypertension will be invited to participate in a cohort study 2 1/2 years after delivery. Participants will be screened for established modifiable cardiovascular risk indicators. The primary outcome is the 10-year cardiovascular event risk. Secondary outcomes include differences in cardiovascular parameters, SNP's in glucose metabolism, and neonatal outcome. Discussion This study will provide evidence on the potential health gains of a modifiable cardiovascular risk factor screening program for women whose pregnancy was complicated by hypertension or preeclampsia. The calculation of individual 10-year cardiovascular event risks will allow identification of those women who will benefit from primary prevention by tailored interventions, at a relatively young age. Trial registration The HYPITAT trial is registered in the clinical trial register as ISRCTN08132825.